CHARACTERIZING THE SOIL FOR IMPROVED NUTRIENT MANAGEMENT IN SELECTED MAIZE GROWING AREAS OF INDONESIA - Fauzi, Achmad I.; Agus, Fahmuddin; Sukarman, Sukarman; Nugroho, Kusumo (Indonesian Agency for Agricultural Research and Development - MOA, 2011)
The demand for maize, the second most important food crop in Indonesia, is steadily increasing. Knowledge of soil properties is a key element in developing nutrient management system. The aims of this study were to characterize and classify the soils at the family level of Soil Taxonomy and linking the taxa with nutrient management systems. The study was conducted at the Site Specific Nutrient Management (SSNM) for maize in Indonesia from June to October 2005. Eight soil profiles were taken from Karo (North Sumatra), Sidomulyo (Lampung), Wonogiri and Grobogan (Central Java), Wonokerto, Mojoayu, and Tuban (East Java), and Jeneponto (South Sulawesi). The soil samples were analyzed for their physical, chemical, and mineralogical characteristics. Soil profile description followed the Standard Guidelines of the Food and Agriculture Organiza-tion. Results showed that the sites for the SSNM represented a wide range of soils and climate characteristics from Entisols with 1,050 mm annual rainfall in Jeneponto to Oxisols with 2,200 mm annual rainfall in Lampung. Most soils had a fine texture class (clay and clay loam), but in places like Lampung and Wonogiri, the clay had a low activity leading to a low cation exchange capacity (CEC) and low exchangeable cations, especially K. The relatively high-K status soils were found in Karo, Grobogan, and Tuban sites. Organic matter and, in consequence, total N were relatively low for all SSNM sites. Available P status ranged from low to high. The low available P in Grobogan, Wonokerto, and Mojoayu soils seemed to be related to high pH, while in Lampung it was due to low pH. Exchangeable Ca and Mg were high in Grobogan, Mojoayu, Karo, and Tuban due to the presence of weatherable minerals such as hypersthene, augite, and hornblende. In general, this study suggests that organic matter, N, and P will be needed across the sites. K addition will be necessary for Karo, Lampung and Wonogiri, while in other SSNM areas, maintenance rates for K will be needed unless plant residues are recycled.